IMR 665: Management of Audio Visual Records & Archives. Individual assignment: Article summary / Wan Nur Nellysa Wan Md Halim - Wan Md Halim, Wan Nur Nellysa (2015)
Article on: Article 1 - “The Public-Private partnership case study in digitization of audiovisual heritage” Article 2 – “Challenges of Digital preservation for cultural heritage institution”